2021
DOI: 10.1016/j.ebiom.2021.103609
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of DNA methylation in 106 schizophrenia family trios in Han Chinese

Abstract: Background: Schizophrenia (SCZ) is a severe psychiatric disorder that affects approximately 0.75% of the global population. Both genetic and environmental factors contribute to development of SCZ. SCZ tends to run in family while both genetic and environmental factor contribute to its etiology. Much evidence suggested that alterations in DNA methylations occurred in SCZ patients. Methods: To investigate potential inheritable pattern of DNA methylation in SCZ family, we performed a genome-wide analysis of DNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In the BATMAN analysis, the methylation status was categorized into three levels: “1” (high, DNA methylation >60%), “0” (moderate, DNA methylation 40–60%) and “-1” (low, DNA methylation <40%) ( Down et al, 2008 ). Probes with poor quality (outlier flag = 1) in >10% of the subjects, associated with cellular specificity ( Jaffe and Irizarry, 2014 ), located on sex chromosomes and BATMAN values for probes that concentrated to one level in >95% of the subjects were excluded from the remaining analyses ( Huai et al, 2019 ; Shen et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the BATMAN analysis, the methylation status was categorized into three levels: “1” (high, DNA methylation >60%), “0” (moderate, DNA methylation 40–60%) and “-1” (low, DNA methylation <40%) ( Down et al, 2008 ). Probes with poor quality (outlier flag = 1) in >10% of the subjects, associated with cellular specificity ( Jaffe and Irizarry, 2014 ), located on sex chromosomes and BATMAN values for probes that concentrated to one level in >95% of the subjects were excluded from the remaining analyses ( Huai et al, 2019 ; Shen et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…To identify the association between differentially methylated positions (DMPs) and PANSS percentage change values, we used linear regression adjusting for age ( Yu H. et al, 2018 ). The identified DMPs were annotated by Table Browser implemented in the UCSC genome browser ( http://genome.ucsc.edu/cgi-bin/hgTables ) ( Shen et al, 2021 ). Differentially methylated regions (DMRs) were determined using comb-p ( Pedersen et al, 2012 ) with a distance of 500 bp and a seeded p -value of .01.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis of schizophrenia and bipolar disorder is also correlated with hypomethylation of the A3 CpG site in both diseases and hypermethylation of the AluY A1 and A2 CpG sites in bipolar disorder [52]. In addition, a methylome-wide analysis of DNA methylation of peripheral blood samples from 106 Chinese schizophrenia family trios, 125 hypomethylated and 112 hypermethylated regions were detected [53]. Another study demonstrated that the development of schizophrenia and intellectual disability is associated with the altered methylation levels of FYN, signal transducer and activator of transcription 3 (STAT3), Ras-related C3 botulinum toxin substrate 1 (Rac1), and nuclear receptor 4A2 (NR4A2) as well as changing function of the immune system [54].…”
Section: Epigenetic Aberrations and Mental Disordersmentioning
confidence: 99%
“… Zhang et al, 2015 ). In addition to the increased variants of NOTCH pathway genes in SZ, epigenetic analysis has revealed evidence of differentially methylated regions of NOTCH pathway genes in SZ patients ( Shen et al, 2021 ).…”
Section: Aberrant Notch Signaling Pathway In Szmentioning
confidence: 99%